Skin Surface Temperature Changes before and after Median Nerve Decompression in Carpal Tunnel Syndrome - Lucija Pavljak; Krešimir Bulić; Maksimilian Mrak; Anko Antabak (Acta Clinica Croatica)
Carpal tunnel syndrome is the most common upper extremity compression neuropathy caused by compression of the median nerve at the wrist. Along with motor and sensory fibers, sympathetic fibers also pass through the median nerve, playing an important role in the regulation of blood flow to the skin which interacts between the body interior and its environment. The aim of this study was to examine the pre- and postoperative correlation between skin temperature changes in the area innervated by compressed median nerve compared to the skin areas innervated by radial and ulnar nerve and median nerve of the unaffected hand. The study included 16 patients with carpal tunnel syndrome with an indication for open carpal tunnel decompression. Skin temperature was measured preoperatively, at 2-week, 2- and 6-month follow-ups on the areas innervated by median, ulnar and radial nerve of the affected hand and median nerve of the non-affected hand. On the affected hand, median nerve innervated skin temperature showed maximum increase at 2-month follow-up before decreasing to a level higher than preoperatively. Radial nerve innervated skin temperature was lower than the preoperative value at 2-week follow-up, increasing to higher levels afterwards. Ulnar nerve temperature followed the curve of the median nerve innervated skin at all follow-ups. Unaffected median nerve innervated skin temperature increased at all follow-ups compared to the preoperative values. In conclusion, two or even five additional measurements should be made after at least one year. The results should be correlated with clinical and electromyoneurography recovery.